Challenges and Opportunities for Policy Formulation of Special Economic Zones in Indonesia: A Review of the Contemporary Systematic Literature - A. Ariyadi Adi; M. Akbar Akbar; Andi Muhammad Ishak Ismail Ishak; Safaruddin Safar (Pencerah, 2026)
This study examines the challenges and opportunities in the formulation of Special Economic Zones policies in Indonesia to support inclusive and sustainable economic growth. This study uses a bibliometric approach with data sources obtained from the Dimensions database, where publications are selected based on the keyword